Strategi Dinas Sosial Dalam Menangani Prostitusi Liar Di Kota Medan - Hutauruk, Icha Novita; Muda, Indra; Batubara, Baby Mashito (Universitas Medan Area, 2024)
This article aims to discuss and disseminate the strategies implemented by the Medan City Social Service in dealing with prostitution fraudsters in Medan City. The problem is resolved on the effectiveness of the control efforts that have been carried out by the Social Service. In order to approach this problem, theoretical references from J. David Hunger and Thomas L. Wheelen are used. Data was collected through observation, interviews, documentation and analyzed qualitatively. This study concludes that there are three programs in the Medan City Social Service originating from the Ministry of Social Affairs which aim to overcome social welfare problems, namely, social rehabilitation programs, social protection and security programs, and social empowerment programs. The Medan City Social Service budget comes from the Medan City Regional Revenue and Expenditure Budget, and this budget is used to carry out control operations against fraudulent prostitution perpetrators. The procedure or stages carried out by the Social Service to deal with fraudulent prostitution is the first to carry out a control operation. Then data collection, documentation and assessment are carried out. and the final stage is to take the perpetrators of lying prostitution to a Social Rehabilitation Home. The guidance carried out by the Medan City Social Service for fraudulent prostitution perpetrators is in the form of providing direction, and developing character and attitudes.